How Will India's Urban Future Affect Social Identities?. (May 2017) - Kapur, Devesh
Urbanisation is as much a social process as it is an economic and spatial process. Cities are sites of social change that offer possibilities for social mobility by disrupting the social stratifications of rural societies. If so, what does India's rapid urbanisation mean for social identities and social cleavages in the country? The article examines some of the principal mechanisms that will determine whether India's urban future lies in a burgeoning cosmopolitan sensibility or in sharpening social cleavages. These include new and varied occupations and patterns of employment, the nature of housing and transportation and, crucially, the nature and role of the middle class. If urbanisation's promise in transforming social identities in India is to be realised, the pattern of urbanisation and urban governance must fundamentally change. India needs many more large cities, which are also better funded and governed, which is unlikely to happen unless the promise of the 74th amendment to the Indian Constitution empowering urban local bodies is realised. The degree to which this will occur will have profound effects on India's urban trajectory—and with it, the very nature of Indian society and its social cleavages.